163k views
1 vote
Question 3 :
-7(x - 4) = -7x + 28​

User Jpaljasma
by
5.1k points

2 Answers

6 votes

Hello there :)

So to solve this equation the first thing you want to do is use distributive property on the left side of the equal sign.

-7(x - 4)

-7 × (x) = -7x

-7 × -4= 28

Once we do that we have our new equation

-7x+28 = -7x+28

now this is where it gets tricky since they are the same equation on both sides. What you want to do next is add 7x to both sides.

-7x+28 = -7x+28

+7x +7x

28=28

Since 28=28, the equation will always be true for any value of x.

All real numbers or (−∞,∞)

User Havenard
by
4.8k points
5 votes

Answer:

x = x

True

Explanation:

First, distribute the -7 by multiplying it by everything inside of the parenthesis.

-7 * x = -7x

-7 * -4 = 28

Now, put it together.

-7x + 28 = -7x + 28

We can already tell the the statement is x = x, which is true, but let's solve it just to make sure.

Isolate the x.

Subtract 28 from each side.

-7x + 28 = -7x + 28

-28 -28

Simplify it.

Divide each side by -7.

-7x = -7x

----- -----

-7 -7

x = x

This is true

User Oscar Apeland
by
5.7k points